2020
DOI: 10.3390/molecules25092212
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antioxidant, Anti-Tyrosinase, and Anti-Hyaluronidase Activity of Morus alba L. Leaf Extract by Pulsed Electric Field Extraction

Abstract: In this study we aimed to compare the chemical composition and biological activity between Morus alba L. leaf extract obtained with 95% v/v ethanol using a pulsed electric field (PEF) and the conventional maceration method. Extracts of M. alba leaves collected from Chiang Mai (CM), Sakon Nakon (SK), and Buriram (BR), Thailand, were investigated for 1-deoxynojirimycin content by high-performance liquid chromatography and for total phenolic content by the Folin–Ciocalteu method. Antioxidant activity was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…The positive impact of PEF and US pre-treatment on the extraction of polyphenols from different plant matrices was also observed in previous works (Barba et al, 2015;Bobinaitė et al, 2015;Chaiyana et al, 2020;Giacometti et al, 2018;Medina-Meza and Barbosa-Canovas, 2015;Pataro et al 2017;Rajha et al, 2019), even though none of them was addressed to investigate the comparative effect of PEF and US technologies on the recovery of polyphenols from oregano and wild thyme herbs. Nevertheless, in agreement with our results, Barba et al (2015) and Rajha et al (2019) observed a greater release of phenolic compounds from PEF pre-treated samples of grape pomace and pomegranate peels, respectively, with respect to those irradiated by US.…”
Section: Accepted Articlesupporting
confidence: 57%
“…The positive impact of PEF and US pre-treatment on the extraction of polyphenols from different plant matrices was also observed in previous works (Barba et al, 2015;Bobinaitė et al, 2015;Chaiyana et al, 2020;Giacometti et al, 2018;Medina-Meza and Barbosa-Canovas, 2015;Pataro et al 2017;Rajha et al, 2019), even though none of them was addressed to investigate the comparative effect of PEF and US technologies on the recovery of polyphenols from oregano and wild thyme herbs. Nevertheless, in agreement with our results, Barba et al (2015) and Rajha et al (2019) observed a greater release of phenolic compounds from PEF pre-treated samples of grape pomace and pomegranate peels, respectively, with respect to those irradiated by US.…”
Section: Accepted Articlesupporting
confidence: 57%
“…Determination of Anti-Aging Activities 2.6.1. Anti-Hyaluronidase Activity Anti-hyaluronidase activity measurement was performed as previously described by Chaiyana et al (2020) [31]. First, 20 µL of oil samples (PSO1, PSO2, COM1, COM2) were mixed with 100 µL of 15 U/mL hyaluronidase solution and incubated at 37 • C for 10 min.…”
Section: Ferric Thiocyanate (Ftc) Assaymentioning
confidence: 99%
“…Kojic acid, the most intensively studied inhibitor of TYR, is a fungal metabolite currently used as a cosmetic skin-whitening agent and as a food additive for preventing enzymatic browning. Kojic acid and arbutin are often used as the positive controls in the literature for comparing the inhibitory strength of the tested inhibitors (Chaiyana et al, 2020;Chang, 2009;Lee et al, 2016). Also, TYR inhibition is considered as one of alternative therapeutical strategies for PD, which acceletate the investigation of medicinal plants as natural source of TYR inhibitors.…”
Section: Potential Of Medicinal Plants In Pd Therapymentioning
confidence: 99%